Permasalahan Pendidikan Anak di Yayasan Panti Asuhan Sinar Damai Sejahtera - Monica Mutiara; Bengkel (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Education is a right that must be obtained by every child without any exceptions. Fulfilling the needs of children is not that easy, because not all children are born in a family that is financially and physically capable of meeting all the needs of their children, some children are born from underprivileged families so that they cannot meet the needs of children, especially in the field of education. These limitations encourage children to experience parenting in an orphanage which is an alternative to child care. at the Orphanage it has not been maximized because the same thing often happens at the Sinar Damai Sejahtera Orphanage Foundation where the children there need help to be able to solve children's problems in the field of education including there are children who cannot write, do not know numbers and the biggest for reading. This problem can arise because of the lack of donors and the children in the orphanage get love because of the lack of caretakers of the orphanage. Various kinds of problems can be overcome in PKL 1 Activity by using the social casework method. Which consists of the stages of engagement, intake & contract, assessment, planning, intervention and termination.